Dietary Niacin Requirement of Juvenile Chinese Mitten Crab, Eriocheir sinensis - Xuran Liu; Wenlong Wan; Mengge Li; Jiayuan Shi; Jie Xu; Zihan Zhou; Anran Wang; Shuyan Miao (Aquaculture Nutrition)
Effects of dietary niacin on the growth performance, intestinal histomorphology, body composition, and antioxidant capacity were investigated in the present study to determine the optimum requirement of niacin for juvenile Eriocheir sinensis. All 360 crabs (initial average weight 1.14±0.04 g) were randomly divided into 6 groups with 3 replicates in each group and 20 crabs in each replicate. Crabs were fed with the control diet (0.89 mg/kg) or niacin-supplemented diets (170.54 mg/kg, 347.05 mg/kg, 587.59 mg/kg, 784.85 mg/kg, and 1248.86 mg/kg) for 12 weeks (named as G1, G2, G3, G4, G5, and G6, respectively). The results showed that appropriate dietary niacin (above 347.05 mg/kg) significantly increased the weight gain rate (WGR) and specific growth rate (SGR) (p<0.05), but did not affect the survival rate (SR), feed conversion ratio (FCR), daily feeding rate (DFR), and molting frequency (MF) of crabs (p>0.05). The niacin content in the hepatopancreas of crabs in G1 and G2 was significantly lower than that of the other four groups (p<0.05). Moreover, dietary niacin significantly affected the intestinal histomorphology of crabs, including the number of folds (NF), height of folds (HF), height of microvillus (HMV), and thickness of muscularis (TM) (p<0.05). Additionally, moderate dietary niacin levels significantly affected the nonspecific immune responses of crabs, by improving the activity of catalase (CAT), glutathione s-transferase (GST), glutathione peroxidase (GSH-Px), and total superoxide dismutase (T-SOD) (p<0.05). Based on the broken-line model analysis of SGR against dietary niacin level, the dietary niacin requirement of juvenile crabs was suggested to be 419.4 mg/kg.